2006
DOI: 10.1111/j.1469-8137.2006.01666.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and translocation of manganese in seedlings of two varieties of Douglas fir (Pseudotsuga menziesii var. viridis and glauca)

Abstract: Summary• Douglas fir ( Pseudotsuga menziesii ) variety glauca (DFG) but not the variety viridis (DFV) showed symptoms of manganese (Mn) toxicity in some field sites. We hypothesized that these two varieties differed in Mn metabolism.• To test this hypothesis, biomass partitioning, Mn concentrations, subcellular localization and 54 Mn-transport were investigated.• Total Mn uptake was three-times higher in DFG than in DFV. DFV retained > 90% of 54 Mn in roots, whereas > 60% was transported to the shoot in DFG. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…(from 0 to 640 mM) in the nutrient solution (Chatzistathis, unpublished data). Differences between genotypes of the same species in growth, absorption, and distribution of Mn within tissues have been also reported by researchers in other species such as soybean, Triticales, and Pseudotsuga menziesii (Ducic et al, 2006;Heenan and Carter, 1976;Quartin et al, 2001) and are in accordance with our results.…”
Section: Discussionsupporting
confidence: 93%
“…(from 0 to 640 mM) in the nutrient solution (Chatzistathis, unpublished data). Differences between genotypes of the same species in growth, absorption, and distribution of Mn within tissues have been also reported by researchers in other species such as soybean, Triticales, and Pseudotsuga menziesii (Ducic et al, 2006;Heenan and Carter, 1976;Quartin et al, 2001) and are in accordance with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it is likely that Mn accumulation is initially rapid within the root, but prolonged translocation to the shoot is important in longer term studies. In observations consistent with this study, Ducic et al (2006) also found an absence of elevated levels of Mn in the vascular system of both tolerant and sensitive Douglas fir varieties. In contrast with Mn in cowpea, however, Zn concentrations in the stele were substantially higher than in the cortex and rhizodermis (Kopittke et al 2011b).…”
Section: Discussionsupporting
confidence: 91%
“…Under Mn-toxicity, the majority of Mn in C. sinensis and C. grandis plants was retained in the roots (Figure 2E), as previously found for C. grandis [8], lucerne [35] and Douglas fir [38]. However, in rice exposed to Mn-toxicity, Mn was predominantly accumulated in leaves compared with roots [39].…”
Section: Discussionsupporting
confidence: 73%